PENGABDIAN KEPADA MASYARAKAT MELALUI PROGRAM KKN DI KAMPUNG MOYANG, DISTRIK PRAFI, KABUPATEN MANOKWARI: Community Service through the KKN Program in Kampung Moyang, Prafi District, Manokwari Regency - Mutakim Takim; Julius D. Nugroho; Mahmud; Imam A. Salim; Luisa N. Laos; Dewi Meilani; Kornelius Kolo; Olce Y. Mandacan; Nari Iwou; Adomina J. Wanggai; Yohanan Y. Mamesah; Yulince M. Awom (IGKOJEI: Jurnal Pengabdian Masyarakat, 2022)
ABSTRACT  This activity aims to identify development problems and find solutions to problems through the establishment of KKN programs to encourage community development in Kampung Moyang, Prafi District, Manokwari Regency. The method of this service activity is through assistance and counseling to the community in the form of training, lectures, and direct socialization in several programs that have been planned based on the results of preliminary observations at the KKN location. The health sector activities carried out are distributing masks and posters of healthy lifestyles, counseling on good and correct toothbrushes, and healthy gymnastics for PKK mothers and children. The field of village administration through the making of PKK program signboards, PKTMB signage boards, 7K signboards, and village administration maps. The environmental sector through community service work activities with residents and the manufacture of trash cans. The field of education through activities introduces letters, numbers, and coloring pictures. In addition, other supporting activities were carried out in the economic and cultural fields, namely through activities to make cassava-based chips with PKK mothers and introduce Papuan folk songs to children. The results of the implementation of the activity showed that training and mentoring, as well as socialization in Kampung Moyang, were able to have a positive impact on increasing the knowledge, attitudes, and skills of the people of Kampung Moyang. The KKN group has been able to identify development problems in Kampung Moyang and has been able to provide solutions for the improvement of Kampung Moyang.  Keywords: KKN; Moyang Village; PKM.   ABSTRAK  Kegiatan ini bertujuan untuk mengidentifikasi permasalahan pembangunan serta mencari solusi pemecahan masalah melalui pembentukan program-program KKN untuk mendorong pembangunan masyarakat di Kampung Moyang Distrik Prafi Kabupaten Manokwari. Metode kegiatan pengabdian ini melalui pendampingan dan penyuluhan kepada masyarakat dalam bentuk pelatihan, ceramah dan sosialisasi secara langsung pada beberapa program yang sudah direncanakan berdasarkan hasil observasi awal di lokasi KKN. Kegiatan bidang kesehatan yang dilaksankan adalah membagikan masker dan poster pola hidup sehat, penyuluhan sikat gigi yang baik dan benar serta senam sehat untuk ibu-ibu PKK dan anak-anak. Bidang administrasi kampung melalui pembuatan papan plang program PKK, papan plang PKTMB, papan plang 7K dan peta adminitrasi kampung. Bidang lingkungan melalui kegiatan kerja bakti bersama warga dan pembuatan tempat sampah. Bidang pendidikan melalui kegiatan memperkenalkan huruf, angka dan mewarnai gambar. Selain itu, dilakukan kegiatan pendukung lainya dalam bidang ekonomi dan budaya yaitu melalui kegiatan pembuatan keripik berbahan dasar singkong bersama ibu-ibu PKK dan memperkenalkan lagu daerah Papua kepada anak-anak. Hasil pelaksanaan kegiatan menunjukan bahwa pelatihan dan pendampingan serta sosialisasi di Kampung Moyang mampu memberikan dampak positif terhadap peningkatan pengetahuan, sikap dan keterampilan masyarakat Kampung Moyang. Kelompok KKN sudah mampu mengidentifikasi permasalahan pembangunan di Kampung Moyang dan sudah mampu memberikan solusi untuk perbaikan Kampung Moyang. Kata kunci: Kampung Moyang; KKN; PKM